Parameters of the internal picture of the disease and quality of life in patients with systemic lupus erythematosus - V. M. Yaltonsky; I. N. Abrosimov; T. D. Andrushkevich; E. M. Shashurina; S. K. Solovyev; E. A. Aseeva (Современная ревматология)
Objective: to analyze the structural features of the internal picture of the disease (IPD in patients with systemic lupus erythematosus (SLE) and its ratio with quality of life (QOL) as an indicator of adaptation to the disease.Patients and methods. The investigation enrolled 51 patients with SLE. Comparison groups included patients differing in the psychological parameter – the perception of the existing disease as a threat to life and health: Group 1 (n=17) regarded their disease as a moderate threat to life and well-being; Group 2 (n=34) considered it as a severe threat.Results and discussion. Comparative analysis of the cognitive level of IPD revealed statistically significant differences between the patients of Groups 1 and 2 in the following scales: «course of the disease» (p<0.001), «personal control» (p<0.001), «treatment control» (p<0.001), «understandability of the disease» (p<0.001), «emotional response to the disease» (p<0.005), and «overall level of disease threats» (p<0.001). It turned out that Group 1 patients better understood the features of the course and manifestation of the disease, were more confident in the efficiency and importance of the treatment prescribed, as well as in their own capabilities to improve their health status. Group 2 patients were more inclined to try to cope with the existing negative experiences, by avoiding the problem.Conclusion. IPD can be different in patients with SLE. The perception of illness as a severe threat negatively affects the efficiency of therapy, mental well-being, social activity, and ultimately QOL. The findings can be used to develop programs for psychological support of patients with rheumatic diseases, in particular those with SLE.